The Functions and Objectives of Islamic Law and Their Correlation with Community Development - Iqbal, Muhammad (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
The function and purpose of Islamic law is often referred to in ushul fiqh with the term maqashid al-syariah as an effort for the welfare of society and realizing the benefit to humans. This study uses a qualitative approach in analyzing, explaining, describing and revealing research results. The data collection technique used was a literature study (library research). This study aims to explore the functions and objectives of Islamic law towards the development of people's daily life, at least knowing the purpose of the law maker (God) to prescribe Islamic law to the community as the executor of the law. This study found that the objectives ofIslamic law are divided into three levels, viz dharuriyyat, pilgrimage andtahsiniyyatThe purpose of Islamic law in terms of benefit is basically divided into 2 namely dharuriyyat and ghairu dharuriyyat This basic benefit is often known by the term kulliyat al-khams(five points/core) namely protection of religion, protection of life, protection of reason, protection of offspring and protection of property. The five points/cores lead to human benefit in this world and in the hereafter. Keyword: Keywords: Purpose of Islamic Law, Function of Islamic Law, Maqashid al-Syariah, Community Building